"Ain't No Hood Like Motherhood": The Complexity of Human Milk Donor Identity. (29th January 2020) - Oreg, Ayelet; Appe, Susan
Abstract : Objective: This article draws on the literature of bodily gifting, the motivations for milk donation, and donor identity to explore human milk donation in the context of nonprofit milk banks. We ask: What are the characteristics of the milk donor identity? Methods: We qualitatively analyze written testimonials and images produced by human milk donors during the time of their milk donation. Results: We found that milk donors comprised complex identities: the identity of a mother, of a woman, sometimes a recipient, and often including the donor's professional identity. Conclusion: Given the increasing demand for human milk donations, studying the unique aspects of this donation is important. The complexity of milk donor identity is captured in the fluidity of human milk donation itself, donors and recipients with this bodily gifting include the babies, mothers, and even entire families.